DIPLOMASI PUBLIK KOREA SELATAN MELALUI PLATFORM DIGITAL KOREA TOURISM ORGANIZATION DALAM MENINGKATKAN KUNJUNGAN WISATAWAN INDONESIA DI ERA NEW NORMAL - Fadhillah Nurlita Ahmad, (2022)
The COVID-19 pandemic that hit South Korea resulted in a very drastic decline in the number of foreign tourist visits, including Indonesian tourists who came to visit South Korea. The South Korean government through the Korea Tourism Organization took initiative steps in the new normal to overcome these problems. The author analyzes using the theory of public diplomacy and the concept of digital tourism. The descriptive qualitative research method explains through complete data how public diplomacy through digital platforms has been carried out. As for the results obtained from this research, South Korea through the Korea Tourism Organization's digital platform, namely Instagram, YouTube, and the website able to increase the number of arrivals of Indonesian tourists who come to South Korea in the new normal. That with the efforts made by KTO through digital platform , it has succeeded in increasing the number of Indonesian tourist visits in the new normal when compared to the same time in the previous year.